Co-pyrolysis of rice straw and Polyethylene Terephthalate (PET) using a fixed bed drop type pyrolyzer - Izzatie, N.I. (Institute of Physics Publishing, 2017)
In this work, co-pyrolysis of rice straw and polyethylene terephthalate (PET) was carried out at different temperatures (450,500,550, and 600°C) at ratio 1:1 by using fixed bed drop-type pyrolyzer. The purpose of this work is to determine the effect of pyrolysis temperature on the product yield. As the temperature increased, the pyrolysis oil increased until it reaches certain high temperature (600°C), the pyrolysis oil decreased as of more NCG were produced. The temperature 550°C is considered as the optimum pyrolysis temperature since it produced the highest amount of pyrolysis oil with 36 wt.. In pyrolysis oil, the calorific value (13.98kJ/g) was low because of the presence of high water content (52.46 wt.). Main chemicals group from pyrolysis oil were an aldehyde, ketones, acids, aromatics, and phenol and all compound have abundant of hydrogen and carbon were identified. Co-pyrolysis of rice straw and PET produced a higher amount of carbon oxides and recycling back the NCG could increase liquid and char yields. © 2017 Published under licence by IOP Publishing Ltd.